Exploring the Application of Information and Communication Technologies in the Acquisition of Information Resources in Three Academic Libraries in North-West Nigeria: Preliminary Findings. Issue 3 (2nd July 2020) - Dahiru, Garba; Oladokun, Olugbade; Grand, Balulwami; Mutshewa, Athulang
Abstract: Information and Communication Technologies (ICTs) incursion has brought a lot of changes to libraries activities. ICTs are used to manage libraries more efficiently and in meeting customers' demands more appropriately at the right time. Despite the contribution of ICTs to library and information work, many libraries are yet to adopt these technologies especially in the acquisitions of library materials. This study was carried out in three selected university libraries in North West Nigeria. The objectives of the study were to: determine the influence of performance expectancy on academic librarians' intention to use ICT for acquisition; establish the influence of effort expectancy on academic librarians' intention to use ICT for acquisition; find out the extent of social influence and facilitating conditions on academic librarians' intention to use ICT for acquisition and lastly to proffer recommendations. This study adopted a positivistic approach and used a questionnaire administered to 224 librarians to collect data in the three selected libraries. The study is guided by the Unified Theory Acceptance and Use of Technology (UTAUT) developed by Venkatesh. Findings from the study reveals that academic librarians are supportive on the use of ICT in their work; ICTs are significantly important, trainings were organized mainly for librarians on general use of ICT not only on acquisition, but also on the general issues related to library activities; librarians also have the knowledge necessary to use ICT for acquisition in their libraries. The study recommends among others that the parent universities should increase the funding of their libraries with adequate supervision, so that such funds are well utilized for ICTs application; university libraries should continually sponsor their academic staff on modern computerized ways of using ICTs to source for materials and the acquisition of information resources in academic libraries should be given all the seriousness it deserves by enacting legislation to allocate a reasonable percentage of the university's budget to it.